2011
DOI: 10.1002/chem.201100807
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Rewritable Memory Effects in Graphene Oxide Functionalized by Conjugated Polymer Containing Fluorene and Carbazole Units

Abstract: A new polymer, poly[{9,9-di(triphenylamine)fluorene}(9,9-dihexylfluorene)(4-aminophenylcarbazole)] (PFCz) was synthesized and used in a reaction with graphene oxide (GO) containing surface-bonded acyl chloride moieties to give a soluble GO-based polymer material GO-PFCz. A bistable electrical switching effect was observed in an electronic device in which the GO-PFCz film was sandwiched between indium-tin oxide (ITO) and Al electrodes. This device exhibited two accessible conductivity states, that is, a low-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…When the trap sites are filled, the conducting paths are erected as a result, the current increases abruptly with the device switching from the OFF state to the ON state. It is found that the ITO/GO-PPy/Al device shows considerably weak OFF-state currents (10 -8 A), more than four orders of magnitude lower than the OFF-state currents of the RRAM devices prepared from the composites of graphene and conducting polymers (10 -3 -10 -4 A) [13][14][15][16]. The low OFF-state current implies that the GO-PPy film owns a plenty of electron trap.…”
Section: The Resistive Switching Memory Propertiesmentioning
confidence: 94%
See 2 more Smart Citations
“…When the trap sites are filled, the conducting paths are erected as a result, the current increases abruptly with the device switching from the OFF state to the ON state. It is found that the ITO/GO-PPy/Al device shows considerably weak OFF-state currents (10 -8 A), more than four orders of magnitude lower than the OFF-state currents of the RRAM devices prepared from the composites of graphene and conducting polymers (10 -3 -10 -4 A) [13][14][15][16]. The low OFF-state current implies that the GO-PPy film owns a plenty of electron trap.…”
Section: The Resistive Switching Memory Propertiesmentioning
confidence: 94%
“…The OFF state of the device can be read (Sweep 4) and reprogrammed to the ON state in the subsequent positive sweep (Sweep 5), thus completing the ''write-read-erase-read-rewrite'' cycle for a nonvolatile rewritable memory device. It is seen that the two resistance states remain stable even after the voltage is removed, indicating the nonvolatile memory [16]. With the ON/OFF current ratio as high as 10 5 , the reversible resistance switching between HRS and LRS promises to be used in the rewritable data storage system.…”
Section: The Interaction Between Ppy and Gomentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene can give rise to bipolar switching [49] and sometimes WORM [50] memory effects. Graphene oxide functionalized with polymer chains gives a solution processable macromolecular material, displaying memory effects in combination with ITO and Al electrodes [51][52][53]. Finally, amorphous carbon and diamond-like carbon are amorphous carbon allotropes that show electronic memory effects in MIM devices.…”
Section: Carbon Allotropesmentioning
confidence: 99%
“…7 In our previous work, we designed a series of D-A-type functional polymers. [8][9][10][11][12][13][14][15][16][17][18][19] The device based on conjugated poly[9,9-bis(4-diphenylaminophenyl)-2,7-fluorene] donors covalently bridged with Disperse Red 1 acceptors (DR1-PDPAF-DR1) exhibited an accessible rewritable memory characteristic. 10,17 The excitation of donor promoted CT to the conjugated channel, finally the electrons were at LUMO1 or further at LUMO2 and gave rise to a conductive charge separation state.…”
Section: Introductionmentioning
confidence: 99%